2019
DOI: 10.1101/727982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A phylogenomic approach reveals a low somatic mutation rate in a long-lived plant

Abstract: evolution of plants, but the rate at which they accumulate is poorly understood, and has 21 been very difficult to measure directly. Here, we demonstrate a novel method to measure 22 somatic mutations in individual plants and use this approach to estimate the somatic 23 mutation rate in a large, long-lived, phenotypically mosaic Eucalyptus melliodora tree. 24Despite being 100 times larger than Arabidopsis, this tree has a per-generation mutation 25

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 39 publications
5
35
1
Order By: Relevance
“…Our estimate of the mutation rate in S. polyrhiza (8.39E-11 per bp per gen.) is similar to the estimates reported by (Xie et al 2016;Hanlon et al 2019;Orr et al 2020). However, duckweeds do appear to exhibit a low mutation rate compared to animals which have limited cell divisions between meiotic events due to a segregated germline.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our estimate of the mutation rate in S. polyrhiza (8.39E-11 per bp per gen.) is similar to the estimates reported by (Xie et al 2016;Hanlon et al 2019;Orr et al 2020). However, duckweeds do appear to exhibit a low mutation rate compared to animals which have limited cell divisions between meiotic events due to a segregated germline.…”
Section: Discussionsupporting
confidence: 87%
“…Duckweed estimated highlighted by red box. References: (Ossowski et al 2010;Lynch 2010;Denver et al 2012;Schrider et al 2013;Weller et al 2014;Zhu et al 2014;Venn et al 2014;Keightley et al 2015;Uchimura et al 2015;Yang et al 2015;Farlow et al 2015;Ness et al 2015;Smeds et al 2016;Xie et al 2016;Besenbacher et al 2016 p.;Feng et al 2017;Liu et al 2017;Oppold and Pfenninger 2017;Flynn et al 2017;Krasovec et al 2017Krasovec et al , 2018Krasovec et al , 2019Hanlon et al 2019;Orr et al 2020)…”
Section: Discussionmentioning
confidence: 99%
“…First, direct observations of plant development at the cellular level indicate that cells destined to form axillary meristems undergo much fewer divisions than other cells from the moment they are produced in the apical meristem, which suggests that the number of cell divisions per branching event, and therefore the number of opportunities for mutations to accumulate, may be lower than previously thought (Burian et al, 2016). Second, estimates of somatic mutation rates per unit of growth tend to be low (Orr et al, 2020). Third, to our knowledge, the only experiment comparing the mutagenicity of meiosis and mitosis was performed by Magni and Von Borstel (1962) in yeast.…”
Section: Evolutionarily Stable Mutation Ratementioning
confidence: 97%
“…Consistent with this view, it was shown at the cellular level that axillary meristems cells are set aside early during the growth of a shoot (Burian et al, 2016), resulting in a number of cell divisions increasing linearly with the number of branching events in trees although the number of terminal branches increases exponentially. Furthermore, multiple studies showed that somatic mutation rates tend to be considerably lower in taller, more long-lived species (Schmid-Siegert et al, 2017;Plomion et al, 2018;Hofmeister et al, 2019;Orr et al, 2020;Wang et al, 2019;Hanlon et al, 2019). For instance, Orr et al (2020) found the somatic mutation rate per generation to be only ten times higher in Eucalyptus melliodora than in Arabidopsis, despite being > times larger in size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation